Effectiveness of injury prevention program using a global systems approach on high-risk movement mechanics for noncontact acl injury - Sheikhi, B.; Letafatkar, A.; Hadadnezhad, M.; Hogg, J. (Sports Health: A Multidisciplinary Approach, 2025)
Background: Injury prevention training using a global systems approach was designed to develop integrated trunk-lower extremity neuromuscular control using whole-body, rotational forces about the vertical Z-axis during simulated sports movements.